Optimization of Small Scale Total Lipid Extraction from Frog Muscle - Nurul Adilah, Ismail (Universiti Malaysia Sarawak (UNIMAS), 2014)
An optimized procedure based on Folch extraction method for extraction of total lipid from frog muscle is proposed. The effect of tissue disruption method (Hand grinding and glass beads), solvent chloroformmethanol ratio (2:1, 1:1 and 2.5:0.5), and sample-weight to solvent ratio (lg: 20ml, lg; 10ml, lg: 40ml) on percentage of lipid recovery was examined. Glass beads beating was shown to be the best method for frog muscle homogenization. Solvent ratio of 1: I was found to yield the highest percentage of lipid recovery. The percentage of lipid recovery was also recorded to be higher when using double volume of solvent. However, the result extracted by using standard Folch volume still falls within the frog lipid muscle range. When performing this extraction, the species of the frog should be maintained for each batch of optimization. It is essential to weigh the sample weight, and test tube weight accurately to avoid systemic error.